The Role of ESG Disclosure in Moderation of the Influence of Capital Structure, Profitability, and Liquidity on the Value of Companies Listed in the ESGL Index in 2020-2024 - Dicky Yulvarizal (PT Keberlanjutan Strategis Indonesia, 2026)
This study aims to analyze the effect of capital structure, profitability, and liquidity on firm value, as well as to examine the role of ESG Disclosure as a moderating variable in companies listed in the ESG Leaders Index (IDXESGL) during the 2020–2024 period. The study employs an explanatory research approach with a quantitative method to obtain information that can be used to address the research problems. The population of this study consists of all companies listed in the IDX ESG Leaders Index (IDXESGL) issued by the Indonesia Stock Exchange (IDX). From the total population, 33 companies met the predetermined sampling criteria and characteristics. This study employed Statistical Product and Service Solutions (SPSS) as the analytical tool to examine the relationships among the research variables. The results indicate that the Debt to Equity Ratio (DER) has a significant effect on Price to Book Value (PBV). These findings suggest that optimally managed debt utilization is capable of increasing firm value through enhanced financing capacity, operational activities, and business growth opportunities. Therefore, a higher DER within an optimal threshold tends to increase firm value. This study also reveals that ESG Disclosure is able to moderate the effect of Debt to Equity Ratio (DER) on Price to Book Value (PBV) by weakening the relationship. This finding indicates that investors not only consider the company’s level of debt utilization but also pay attention to sustainability factors and corporate risks through ESG disclosure practices.